2021
DOI: 10.3390/diagnostics11030426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Sera from Individuals after S-Gene RNA-Based SARS-CoV-2 Vaccination with Spike-Protein-Based and Nucleocapsid-Based Serological Assays

Abstract: Due to the beginning of vaccination against COVID-19, serological discrimination between vaccine-associated humoral response and serology-based surveillance of natural SARS-CoV-2 infections as well as breakthrough infections becomes an issue of relevance. Here, we assessed the differentiated effects of the application of an RNA vaccine using SARS-CoV-2 spike protein epitopes on the results of both anti-spike protein–based serology (EUROIMMUN) and anti-nucleocapsid-based serology (VIROTECH). A total of 80 serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
6
26
2
2
Order By: Relevance
“…Overall, the identification of three important predictors (age, sex, baseline serostatus) of post-COVID-19 mRNA BNT162b2 vaccine humoral response in our population of healthcare workers may have some substantial implications and consequences for vaccine plans. Unlike the recent study of Dörschug et al [21], who used a spike protein-based IgG serological immunoassay for monitoring humoral response to COVID-19 mRNA BNT162b2 vaccine and failed to find significant differences between sexes, we found that women had a significantly higher response (between 1.15-1.20-fold higher compared to men) of total anti-SARS-CoV-2 RBD antibodies, especially after the second vaccine dose. This agrees with recent data published by Terpos et al [22], who also found that the anti-Spike-RBD IgGs response was more sustained in female than in male octogenarians after vaccination with Pfizer BNT162b2 mRNA vaccine.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the identification of three important predictors (age, sex, baseline serostatus) of post-COVID-19 mRNA BNT162b2 vaccine humoral response in our population of healthcare workers may have some substantial implications and consequences for vaccine plans. Unlike the recent study of Dörschug et al [21], who used a spike protein-based IgG serological immunoassay for monitoring humoral response to COVID-19 mRNA BNT162b2 vaccine and failed to find significant differences between sexes, we found that women had a significantly higher response (between 1.15-1.20-fold higher compared to men) of total anti-SARS-CoV-2 RBD antibodies, especially after the second vaccine dose. This agrees with recent data published by Terpos et al [22], who also found that the anti-Spike-RBD IgGs response was more sustained in female than in male octogenarians after vaccination with Pfizer BNT162b2 mRNA vaccine.…”
Section: Discussioncontrasting
confidence: 99%
“…Priming dose responders in the present study assessed with the same assay but in semiquantitative fashion had a median of at least 250 U/mL 28 days after D2, making their antibody response at least as robust as healthy individuals 3 weeks from series completion. Another study of 27 healthy individuals who received one or two doses of SARS-CoV-2 mRNA vaccine reported median results of 3.3 at 19 days post-D1 and 6.1 at 3 days post-D2 using an anti-S1 immunoassay (EUROIMMUN) ( 33 ). Priming dose responders in the present study assessed with the same assay had median results of 2.4 at 20 days and 9.3 at 28 days following D1 and D2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the recent studies of Salvagno et al [ 18 ] and Terpos et al [ 22 ], where the anti-Spike-RBD IgGs response was also observed to be more sustained in females than in males after vaccination with BNT162b2 vaccine. Another study, where the Euroimmun anti-SARS-CoV-2 S1 IgG ELISA assay was used to monitor humoral response to COVID-19 mRNA BNT162b2 vaccine, did not show any statistically significant correlation between the age and sex of the individuals and the immune response caused by the vaccine [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently reported higher morbidity and mortality of SARS-CoV-2 infection in women and people of older age, excluding children younger than 5 years old that are also vulnerable [ 19 , 20 , 21 ]. However, concerning the impact of age and sex on vaccine efficiency, the data so far are limited and contradictory [ 18 , 22 , 23 , 24 , 25 , 26 , 27 ]. Thus, more experiments should be conducted to determine this relationship.…”
Section: Introductionmentioning
confidence: 99%